Effect of perlite on specific cake resistance in constant pressure filtration of pectin extract from orange peel - Arslan, N; Kar, F (Assn Food Scient Techn India, 1998)
The pectin extract was vacuum-filtered at 15 degrees C under various pressure differences (0.20x10(5) Pa 0.33x10(5) Pa and 0.47x10(5) Pa), and the specific cake resistances were determined. Specific cake resistance was dependent on the filtration pressure. The cake compressibility coefficient at 15 degrees C were calculated as 0.783. It was found that the cake obtained from constant pressure filtration of pectin extract from orange peel was compressible. The effects of precoating amount and filter aid dose on specific cake resistance were studied. Pre-coating the filter medium with perlite increased specific cake resistance. A decrease was observed in specific cake resistance with increasing filter aid concentrations. A further decrease was obtained at specific cake resistance, when precoating and filter aid were used together. The equipment used in the present study to measure average specific cake resistance is also discussed.
Keywords: orange peel; pectin; filtration; perlite; specific cake resistance